Exploitation of CD3ζ to enhance TCR expression levels and antigen-specific T cell function - Degirmencay, Abdullah; Thomas, Sharyn; Holler, Angelika; Burgess, Samuel; Morris, Emma C.; Stauss, Hans J. (Frontiers in Immunology, 2024)
The expression levels of TCRs on the surface of human T cells define the avidity of TCR-HLA/peptide interactions. In this study, we have explored which components of the TCR-CD3 complex are involved in determining the surface expression levels of TCRs in primary human T cells. The results show that there is a surplus of endogenous TCR α/β chains that can be mobilised by providing T cells with additional CD3γ,δ,ε,ζ chains, which leads to a 5-fold increase in TCR α/β surface expression. The analysis of individual CD3 chains revealed that provision of additional ζ chain alone was sufficient to achieve a 3-fold increase in endogenous TCR expression. Similarly, CD3ζ also limits the expression levels of exogenous TCRs transduced into primary human T cells. Interestingly, transduction with TCR plus CD3ζ not only increased surface expression of the introduced TCR, but it also reduced mispairing with endogenous TCR chains, resulting in improved antigen-specific function. TCR reconstitution experiments in HEK293T cells that do not express endogenous TCR or CD3 showed that TCRα/β and all four CD3 chains were required for optimal surface expression, while in the absence of CD3ζ the TCR expression was reduced by 50%. Together, the data show that CD3ζ is a key regulator of TCR expression levels in human T cells, and that gene transfer of exogenous TCR plus CD3ζ improved TCR surface expression, reduced TCR mispairing and increased antigen-specific function.